WOMEN'S ENTREPRENEURSHIP AND IMPLEMENTATION OF MARKET ORIENTATION MODEL TO IMPROVE BUSINESS PERFORMANCE OF SMES BATIK JAMBI - Ade Octavia; Zulfanetti Zulfanetti; Yayuk Sriayudha; Heriberta Heriberta (Dinasti International Journal of Education Management And Social Science, 2021)
Investigating of market orientation relationships and business performance has been widely conducted, but the research related to the implementation of the market-business performance orientation model is still relatively rarely. A woman entrepreneur who accepts challenging roles to meet her personal needs and become economically independent is an important role in economic independence. The research aims to analyze how the role of women entrepreneurs in applying market orientation models to improve business performance in SMEs of Batik Jambi in Jambi City. The method used in this study is qualitative method. The results of this study found that SMEs batik Jambi is mostly owned and managed by women entrepreneurs. They have been market oriented and impacted on business performance. Orientation to consumers is a strength factor for women to run their business and they tend to be more responsive to what competitors do. This study found that women entrepreneurs have the ability to coordinate internally. This becomes an internal force for SMEs to improve business performance as well. Lack of the competence in tecnology and information is one of women deficiency that need to be develpo in order to gain competitive advantage among them.